Enduring elites in quoted sources: Institutional alignment in Finnish media, 1999–2018 - Seuri Olli; Koivunen Anu; Levola Henna; Mäkelä Eetu (Nordicom Review)
This article addresses the question of whether and how sourcing practices of journalistic news media have been transformed by online-first publishing and the hybridisation of the media system. Focusing on four Finnish news outlets from 1999 to 2018 (a daily newspaper, a news agency, a tabloid, and a public broadcaster), we analyse the essential gatekeeping practice of giving voice to actors by quoting them directly or indirectly. According to our data, the hybrid media context does not lead to an increased diversification of sources. Instead, our analysis indicates a concentration and consolidation of sources across different news outlets: a continued elite source dominance in domestic political news. This development we term institutional alignment, suggesting that, by foregrounding elite sources, the news media seeks to maintain both its gatekeeping function and its key position in networks of power.